2021
DOI: 10.1002/hed.26635
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of nimotuzumab (TheraCim‐hR3) concurrent with cisplatin/radiotherapy in patients with locally advanced head and neck squamous cell carcinoma

Abstract: Background The efficacy of a combination of nimotuzumab, a humanized monoclonal antibody to the epidermal growth factor receptor, with chemoradiation in locally advanced head and neck squamous cell carcinoma (HNSCC) was evaluated in a phase II study. Methods Patients with stage III/IV HNSCC received 3‐weekly cisplatin 100 mg/m2 for three cycles and weekly nimotuzumab 200 mg for 8 weeks concurrently with radiotherapy. Primary endpoint was best overall response (BOR) and secondary endpoint was progression‐free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…In this regard, a modest efficacy in terms of clinical outcomes has been reported for the fully human anti-EGFR antibodies Panitumumab and Zalutumumab, and for Duligotuzumab, a dual-action antibody directed against EGFR and ErbB3 ( 115 ). Among the anti-EGFR therapeutic antibodies, some encouraging results have instead been obtained with Nimotuzumab, whose binding requires that EGFR is expressed at high density on the surface of the target cells, thus resulting in selective activity on EGFR-overexpressing tumor cells as compared to normal cells ( 115 , 121 ). As for ErbB receptors TKIs, Gefitinib and Erlotinib, which act as reversible inhibitors of EGFR, and Lapatinib, a reversible inhibitor of both EGFR and ErbB2, have also shown a modest activity in HNSCC patients ( 1 , 115 ).…”
Section: Erbb Receptors and Therapy Of Hnsccmentioning
confidence: 99%
“…In this regard, a modest efficacy in terms of clinical outcomes has been reported for the fully human anti-EGFR antibodies Panitumumab and Zalutumumab, and for Duligotuzumab, a dual-action antibody directed against EGFR and ErbB3 ( 115 ). Among the anti-EGFR therapeutic antibodies, some encouraging results have instead been obtained with Nimotuzumab, whose binding requires that EGFR is expressed at high density on the surface of the target cells, thus resulting in selective activity on EGFR-overexpressing tumor cells as compared to normal cells ( 115 , 121 ). As for ErbB receptors TKIs, Gefitinib and Erlotinib, which act as reversible inhibitors of EGFR, and Lapatinib, a reversible inhibitor of both EGFR and ErbB2, have also shown a modest activity in HNSCC patients ( 1 , 115 ).…”
Section: Erbb Receptors and Therapy Of Hnsccmentioning
confidence: 99%
“…Consequently, this limitation may contribute to the observed absence of correlation between EGFR expression levels and the response to EGFR-targeting therapies [ 114 ]. mAbs targeting EGFR have been reported to induce NK-dependent ADCC, while activating CD8+ T-cell responses [ 115 , 116 ]. Therefore, it is suggested that low levels of lymphocytes can have an impact on mAbs efficacy.…”
Section: New Combinatorial Approaches For Oral Cancer Treatmentmentioning
confidence: 99%
“…A number of additional anti-EGFR antibodies have been recently developed and clinically tested, such as Panitumumab [ 142 , 143 , 144 ], Nimotuzumab [ 145 , 146 , 147 ], and Sym004 [ 148 , 149 ]. The anti-EGFR antibody Panitumumab was shown moderate activity as a single agent in HNSCC patients, previously treated with platinum-based drugs [ 142 ].…”
Section: Targeting Oncogenic Pathways In Hnsccmentioning
confidence: 99%
“…The anti-EGFR antibody Panitumumab was shown moderate activity as a single agent in HNSCC patients, previously treated with platinum-based drugs [ 142 ]. The benefits of adding Nimotuzumab to combination therapy with cisplatin and radiotherapy have been reported in some HNSCC patients [ 146 ], and high HIF1α (hypoxia-inducible factor 1-alpha) expression may indicate likely benefit for such treatments [ 145 ]. Sym004 has been in development for at least 10 years, and represents a mix of two chimeric monoclonal antibodies [ 150 ].…”
Section: Targeting Oncogenic Pathways In Hnsccmentioning
confidence: 99%